Internalizing and externalizing behavior in adolescents - Alarcón Parco, Danitsa (2015)
Adolescence is a period of rapid changes in all aspects of human development. It is at this stage that difficulties and mental health problems occur more often. The purpose of the study was to identify both internalizing and externalizing behavior reported by adolescent in high school. The sample was composed by 298 participants between 12 and 18 years old (M = 14.98, SD = 1.28), of both sexes, (54.4 % women) from two public educational institutions where the majority was enrolled in the 4th year of high school (33.6 %). The sample was selected in a non-probabilistic manner for convenience, and all the participants were informed of the purpose and activities of the study, of the voluntary nature of their participation, and of the care to preserve the anonymity and confidentiality of all data collected. We used the self-report of young people between 11 and 18 years old (YSR 11-18, Achenbach and Rescorla, 2001) to identify the internalizing and externalizing behavior and their respective dimensions. The results show significant differences according to sex. Women scored higher than men in anxiety-depression, somatic complaints, attention problems, and internalizing behavior; while men scored higher in breaking the rules, and externalizing behavior.